Build a large language model (from scratch) - Raschka, Sebastian (Manning Publications, 2025)
Build a Large Language Model (From Scratch) is a practical and eminently-satisfying hands-on journey into the foundations of generative AI. Without relying on any existing LLM libraries, you'll code a base model, evolve it into a text classifier, and ultimately create a chatbot that can follow your conversational instructions. And you'll really understand it because you built it yourself!
Keywords: Artificial intelligence; Natural language processing (Computer science); Intelligence artificielle; Traitement automatique des langues naturelles; artificial intelligence